Faktor-Faktor Yang Mempengaruhi Pemilihan Bank Pada Generasi Milenial Di Jabodetabek - Anindia Indah Permata; Martinus Rosadi Nugroho; Elias Sugita Handoyo; Ivan Angga Kusuma (Universitas Prasetiya Mulya, 2018)
This paper aims to determine factors that influence millennials generation at Jabodetabek in selecting a bank for their financial transaction. The significance level on banking selection criteria such as people influence, location, facilities offered, bank personnel, easiness in the process, quality of services, and the cost was also being researched. This study describes how customer ranks these factors by their priorities. The total sample of this study is 224 samples from millennials generation (born during 1980-2000) domiciled at Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek). This study finds that convenient ATM location is the main factor for millennials at Jabodetabek in selecting a bank for their financial transaction